Is Tax the Same as Zakat? A Netnographic Study of Public Perceptions on TikTok - Pasolo, Muhammad Ridhwansyah; Pasolo, Fahrudin (Universitas Trunojoyo Madura, 2025)
Social media platforms in Indonesia, a country with a large Muslim population, have become important spaces for public debate on the relationship between religion and government policy. This study examines public reactions to a statement by the Minister of Finance that framed tax payments as comparable to Islamic zakat obligations, using a qualitative netnographic approach to analyze 29,014 comments from viral TikTok post by a news outlet. The analysis explores how digital publics interpret fiscal claims through moral and religious reasoning, express dissent, and assess governmental legitimacy. Grounded theory inspired coding identifies three dominant patterns: emotional resistance expressed through humor and outrage; moral and religious contestation emphasizing the distinction between sacred obligations and civic duties; and socioeconomic distrust linked to perceptions of inequality and corruption. These reactions indicate a crisis of fiscal legitimacy in the digital sphere, driven by a mismatch between state communication and deeply held public values. The findings suggest that effective fiscal governance requires transparent and value sensitive communication that respects religious boundaries rather than asserting equivalence. This study contributes to debates on legitimacy and moral economy in digital contexts and offers practical insights for improving public finance communication in religiously diverse societies.